Structural characteristics and physicochemical properties of okara (soybean residue) insoluble dietary fiber modified by high-energy wet media milling. (1st September 2017) - Ullah, Ikram; Yin, Tao; Xiong, Shanbai; Zhang, Jin; Din, Zia-ud; Zhang, Mengling
Abstract: Changes in structural characteristics and physicochemical properties of okara insoluble dietary fiber (IDF) during high-energy wet media milling process were analyzed. Particle size of the IDF was effectively reduced from 66.7 μm to 544.3 nm after 6 h of milling and kept constant (p > 0.05) as the milling process prolonged. As the particle size decreased, lightness and whiteness of the IDF significantly (p < 0.05) increased, zeta potential decreased continuously (p < 0.05). Swelling power, water solubility index and apparent viscosity extensively increased (p < 0.05) after 1 h of milling and then steadily decreased (p < 0.05). Electron microscopy observations showed that the IDF was changed from regular and compact rods to aggregates with puffed morphology. Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis revealed that intermolecular hydrogen bonds and crystalline structure of the IDF polysaccharides were disturbed after milling. Graphical abstract: Highlights: Okara insoluble dietary fiber (IDF) was downsized to nanometer range by wet milling. Molecular and crystalline structure of IDF was disrupted after milling. Particle size reduction of the IDF contributed to modify physicochemical properties. Modified okara IDF may be applied as functional ingredient in foods.